Investigação do limite entre domínios geocronológicos da região do médio Rio Xingu, sudeste do Cráton Amazônico - MONTEIRO, Pablo Condurú (Universidade Federal do Pará, 2022)
The Central Amazon Province (PAC), the oldest portion of the Amazon Craton, is admitted as a domain of Archean evolution. This domain, cratonized from the Paleoproterozoic onwards, would be bordered by successive Proterozoic geochronological provinces (2.25 to 0.9 Ga), such as the Maroni-Itacaiúnas Province, progressively younger towards the southwest of the craton. The CAP is divided into two blocks: Carajás and Xingu-Iricoumé, whose boundaries are poorly defined. Today, it is known that the Carajás block has its evolution reported to the Arqueano. The Xingu-Iricoumé block lacks data to characterize its evolution. The general objective of this dissertation is the characterization of the crustal evolution and the evaluation of the boundary between the Central Amazon Province (Carajás or Xingu-Iricoumé blocks) and the Maroni-Itacaiúnas in an area in the middle course of the Xingu River (PA) through geochronological studies. and isotopic geochemistry of igneous and orthometamorphic bodies. To achieve this, we resorted to: construction of a cartographic base through data obtained in previous surveys and in a field campaign; individualization of different types of rocks; determination of crystallization and mantle extraction ages of different igneous rocks and protoliths of metamorphic rocks, as well as the metamorphism that affected them, through the application of Pb-Pb methods in zircon and Sm-Nd in whole rock and garnet. The petrographic studies and field features made it possible to define, within the work area, eight main rocky domains, which are: inequegranular granodiorites, gneisses (enderbitic, tonalitic and peraluminous), charnochites, enderbites, migmatitic gneisses, Iriri-type volcanics, Maloquinha-type granites and, finally, Parauarí-type granodiorite. A set of 19 isotopic data was generated by the Pb-Pb methods in zircon (6) and Sm-Nd total rock and garnet (13), in 13 samples of 6 units. These data aim to bring new geochronological references to the key units and establish a chronology for the events that occurred in the area. The Pb-Pb ages in zircon for the units in the middle Xingu region allowed us to define that they were formed in a short time interval of less than 40 Ma (2.07 - 2.11 Ga). The Sm-Nd isotopic results in whole rock indicated T(DM) model ages with values ​​within the Archean in the range of 2.60 to 3.09 Ga. Thus, the studied rocks were originated by the regeneration of older continental crust, at least 500 Ma, but reaching values ​​of up to about 1.0 Ga. The application of the Sm-Nd method in the garnet-total rock pair of a leukomonzogranitic injection in gneisses indicated an age of 1962 ± 15 Ma, interpreted as the minimum age of the peak of the metamorphism that affected the region. The dataset presented shows that in the studied region there was a Paleoproterozoic magmatism of varied composition linked to a tectonic-thermal event of regional expression – the Transamazonian Cycle. With this, it is confirmed that the region falls within the Maroni-Itacaiúnas Geochronological Province, as previously raised by several authors, and its boundary with the PAC must be in the south of the studied area.